Antibacterial Activity Monascus purpureus (Red pigment) Isolated from Rice Malt - kumar, Ajay; verma, Usha; sharma, Heena (Asian Journal of Biological and Life Sciences, 2012)
Biopigments are such microbial product which has greater impact over chemically synthetic pigments. Certain organism like Monascus purpureus has the ability to produce monascidin Acompound which are red coloured pigments, having antimicrobial properties. The aim of this work was to produce biopigments from organic waste to bring down the production cost and to reduce the organic load from the environment and use the product as antibacterial agent. Rice malt was used as substrate for the production of red pigment using Monascus purpureus. Pigment production was achieved at o 30 C on 10 days of incubation and at pH of 6. The pigments were obtained effectively using ethanol as a solvent and check out the antibacterial activity of pigments against pathogenic and nonpathogenic bacteria i.e. Escherichia coli, Bacillus subtilis, Bacillus megaterium and Pseudomonas aeruginosa.